Study of the landscape of the Hakari River in the climatic conditions of Azerbaijan - Mekhtiyeva Banovsha; Abdullayeva Maya (BIO Web of Conferences)
The article investigates changes in landscape structure due to anthropogenic factors in the Karabakh region of Azerbaijan. The main part of the research object has been exploited for more than 30 years, and its forest-vegetation and soil cover have undergone significant changes. The uncontrolled and chaotic use of objects located in these areas has caused sharp changes in many ecological parameters. The purpose of the research is dedicated to investigating changes in landscape structure in the Hakaririver river basin of Karabakh as a result of anthropogenic impacts. The article uses Geographic Information System (GIS) technology to identify and analyze these changes. The research was conducted in 2 stages. In the first stage, changes in forest-vegetation cover in the Hakaririver basin between 2005 and 2024 were studied using the vegetation index (NDVI). In the second stage, changes in landscape structure in the research area between 1991 and 2021 were investigated and map-schemes were compiled. Using the NDVI index, it was possible to detect significant changes in the properties of soil and vegetation. With a normalized difference vegetation index value, it is possible to calculate certain empirical correlations on the land surface (including vegetation type and quality).